2016
DOI: 10.3892/mmr.2016.5566
|View full text |Cite
|
Sign up to set email alerts
|

miR-22-5p revealed as a potential biomarker involved in the acute phase of myocardial infarction via profiling of circulating microRNAs

Abstract: Acute myocardial infarction (AMI) is a life-threatening episode of coronary artery disease. Recently, circulating myocardial-derived microRNAs (miRNAs) have been reported as potential biomarkers of infarction. The present study aimed to identify differentially expressed miRNAs in patients with ST-segment elevation myocardial infarction that could be potentially dysregulated in response to early myocardial damage. miRNA expression profile analysis was performed using the Serum/Plasma Focus miRNA Polymerase Chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…The plasma and serum samples were stored at −80 °C until analysis. Assessment of hemolysis in the samples was performed as described previously 39 .…”
Section: Methodsmentioning
confidence: 99%
“…The plasma and serum samples were stored at −80 °C until analysis. Assessment of hemolysis in the samples was performed as described previously 39 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the nuclease-resistant extracellular miRNAs have been found that they are present in human blood plasma [9, 10], and displayed some characteristics of an ideal biomarker. There are a mounting number of reports identifying specific plasma miRNAs as potential biomarkers including cancer [11], heart failure [12], myocardial infarction [13] and so on. However, few studies have explored plasma miRNAs expression difference in KD patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the expression level of circulating miR-134-5p in patients with ACS or early AMI was significantly increased [37,52]. The expression of miR-22-5p in plasma of patients with AMI was significantly decreased [76], but the expression of miR-22-5p in serum was significantly increased [77]. The expression of circulating miR-423-5p was downregulated within 24 hours in AMI patients [78], but increased within 6 hours in STEMI, unstable angina, and even AMI patients [26,56,79].…”
Section: Resultsmentioning
confidence: 94%